Preparation method and application of a bayberry-shaped iron-doped cobalt-based chalcogenide nitrogen-doped carbon porous composite material

Through bayberry-like iron-doped cobalt-based chalcogenide nitrogen-doped carbon porous composite, the problem of cobalt-based chalcogenide insufficient volume expansion and conductivity in sodium ion batteries is solved, and long cycle life and good electrochemical performance are achieved .

CN115425209BActive Publication Date: 2024-12-27ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211186912.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-26
Publication Date
2024-12-27
Estimated Expiration
2042-09-26

AI Technical Summary

Technical Problem

The irreversible volume changes of cobalt-based chalcogenides during electrochemical reactions lead to electrode agglomeration and powderization, and the slow diffusion kinetics, limiting their large-scale application in sodium ion batteries.

Method used

Using bayberry-like iron-doped cobalt-based chalcogenide nitrogen-doped carbon porous composite material, the volume expansion effect is alleviated and the conductivity is improved, forming a continuous conductive network and abundant activity by introducing a stable Prussian blue frame structure and porous carbon layer. loci.

Benefits of technology

It extends the cycle life of the negative electrode material of sodium ion battery, improves electrochemical performance, and enhances the charge diffusion rate and electron conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115425209B_ABST
    Figure CN115425209B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of sodium ion batteries, and discloses a preparation method and application of a bayberry-shaped iron-doped cobalt-based sulfide nitrogen-doped carbon porous composite material. The present invention uses zinc salt, iron salt, F127, PVP and potassium cobalt cyanide as raw materials to perform a room temperature precipitation reaction to generate a FeZnCo-PBA precursor; after heat treatment under a protective atmosphere, it is further gas-phase sulfurized (selenized) with sulfur powder or selenium powder to obtain an iron-doped cobalt-based sulfide nitrogen-doped carbon porous composite material. The present invention organically combines a variety of means to alleviate the volume expansion effect of cobalt-based sulfide during the charge and discharge process and improve its conductivity, so that the composite material has a long cycle life and good electrochemical performance when used as a negative electrode material for a sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a preparation method and application of a bayberry-shaped iron-doped cobalt-based sulfide nitrogen-doped carbon porous composite material. Background Art

[0002] As fossil energy is being consumed and depleted, finding alternative clean energy is a key issue that needs to be solved for the long-term survival of human development and the earth's ecological environment. Among them, the development of efficient and stable energy storage and conversion methods has become a hot research direction at present and in the future. However, the very limited lithium resources limit the currently widely used lithium-ion batteries. Sodium-ion batteries have received widespread attention from researchers in recent years because they have similar energy storage mechanisms to lithium-ion batteries, and sodium resources are abundant and the cost of acquisition is low. Since the radius of sodium ions is larger than that of lithium ions, sodium ions tend to occupy interstitial sites with larger spaces during the embedding process. Therefore, finding suitable sodium-embedded host materials is the key to the development of sodium-ion batteries.

[0003] As a conversion-type sodium storage material, cobalt-based chalcogenides have attracted the attention of researchers for their high theoretical specific capacity, narrower bandgap than oxides, easier metal-S (Se) bonds to break than metal-O bonds, and higher first-cycle efficiency. However, the irreversible volume changes produced during the electrochemical reaction will cause the electrodes to agglomerate and pulverize, thereby shortening the service life of the electrodes. Secondly, as an electrode material, it has slow diffusion kinetics, which limits the large-scale application of cobalt-based chalcogenide electrodes. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a preparation method and application of a bayberry-shaped iron-doped cobalt-based chalcogenide nitrogen-doped carbon porous composite material. The present invention organically combines multiple means to alleviate the volume expansion effect of cobalt-based chalcogenide during the charge and discharge process and improve its conductivity, so that the composite material has a long cycle life and good electrochemical performance when used as a negative electrode material for sodium ion batteries.

[0005] The specific technical scheme of the present invention is:

[0006] In a first aspect, the present invention provides a method for preparing a bayberry-like iron-doped cobalt-based chalcogenide nitrogen-doped carbon porous composite material, comprising the following steps:

[0007] (1) Zinc salt, iron salt, polyvinyl pyrrolidone (PVP) and Pluronic F-127 (F127) are added to water and stirred to obtain a yellow transparent solution A.

[0008] (2) Potassium cobalt cyanide is dissolved in water by ultrasonication to obtain a transparent solution B. Under continuous stirring, the transparent solution B is dropped into the yellow transparent solution A to form a yellow transparent solution C.

[0009] (3) The transparent solution C obtained in step (2) is placed in an ice water bath and sonicated to obtain a suspension C.

[0010] (4) The suspension C obtained in step (3) is allowed to stand, and then washed and dried to obtain a light yellow powder α, which is a bayberry-like FeZnCo-PBA precursor.

[0011] (5) The light yellow powder α obtained in step (4) is subjected to heat treatment under a protective atmosphere to obtain a black powder β, i.e., an iron / cobalt / carbon composite material.

[0012] (6) heat-treating the black powder β obtained in step (5) with sulfur powder or selenium powder under inert gas protection to obtain black powder γ, i.e., myrica-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material or myrica-like iron-doped cobalt diselenide / nitrogen-doped carbon porous composite material.

[0013] In the above steps, the main reactions are as follows: first, metal ions react with cobalt cyanide to generate FeZnCo-PBA Prussian blue, wherein the role of PVP is to prevent zinc and iron metal ions from reacting with cobalt cyanide too quickly; then the precursor is subjected to high-temperature carbonization treatment, during which zinc sublimates and loses to form pores, while F127 and PVP react and decompose into carbon, and metallic cobalt is obtained under carbon reduction to obtain nitrogen-doped carbon balls doped with iron-doped cobalt metal; finally, it is subjected to sulfurization (selenization) treatment, and the metallic cobalt is sulfurized (selenized) into cobalt disulfide (cobalt diselenide), to obtain an iron-doped cobalt disulfide (cobalt diselenide) / nitrogen-doped carbon porous composite material, which exhibits a bayberry-like morphology and porous structural characteristics, and the particle size is about 0.5-0.9μm.

[0014] The present invention team found that if the cobalt-based chalcogenide is directly compounded with the carbon material, or the cobalt-based chalcogenide is carbon-coated, the interface coupling between them is weak, and the two are easy to peel off and separate, resulting in a decrease in cycle life. To this end, the present invention solves this technical problem through the following aspects:

[0015] For the first time, the present invention uses FeZnCo-PBA with uniform particles as a precursor, introduces a stable Prussian blue framework structure under the joint action of the structure-directing agent PVP and the porous template F127, and the carbon framework obtained after heat treatment provides a continuous conductive network for the cobalt-based chalcogenide, which can improve the overall structural stability of the composite material. Different from the reported common cubic Prussian blue framework structure, the FeZnCo-PBA of the present invention is in the shape of bayberry, which has the advantage of being more stable in structure, larger in specific surface area, and easier to alleviate volume expansion than the common cubic Prussian blue.

[0016] Secondly, the porous carbon layer in the present invention alleviates the volume expansion effect of cobalt-based chalcogenides during charge and discharge; the porous structure derived from FeZnCo-PBA effectively increases the contact area between the active material and the electrolyte, provides abundant active sites and transmission channels, and promotes ion migration. Due to the introduction of iron ions, a part of the iron ions replace the position of cobalt ions, and the electronic conductivity of cobalt disulfide (cobalt diselenide) is further improved through synergistic effects.

[0017] In addition, the present invention utilizes the synergistic effect of the nitrogen-doped carbon matrix to broaden the charge transfer path, which can further increase the charge diffusion rate.

[0018] In summary, the porous carbon framework material prepared by the present invention has the advantages of being more solid and having more pores than other types of porous carbon frameworks. It is not only zinc ions that sublimate to form pores, but F127 also has the ability to form pores as a pore-forming agent. Using cyanide in PVP and potassium cobalt cyanide as a nitrogen source, nitrogen doping is beneficial to enhancing conductivity. F127 and PVP are used as carbon sources, and the carbon content is richer. The present invention organically combines multiple means to alleviate the volume expansion effect of cobalt-based sulfide during the charge and discharge process and improve its conductivity, so that the composite material has a long cycle life and good electrochemical performance when used as a negative electrode material for sodium ion batteries.

[0019] Preferably, in steps (1) and (2),

[0020] Fe 3+ and Zn 2+ The molar ratio is 1:15-1:3;

[0021] The mass ratio of PVP to Pluronic F-127 is 1.8:1-3.6:1;

[0022] The total molar ratio of potassium cobalt cyanide to metal ions is 4:5-2:3;

[0023] The mass ratio of potassium cobalt cyanide to PVP is 1:4-1:10.

[0024] In order to obtain a bayberry-like Prussian blue structure, the presence of zinc ions and the content of PVP and F127 are crucial. Specifically, we found that other metal salts (except zinc) with ferrocyanide and cobalt cyanide generate a three-dimensional square structure of Prussian blue, while zinc salts with ferrocyanide and cobalt cyanide and an appropriate amount of PVP generate a spherical structure of Prussian blue. On this basis, if you want to further obtain a bayberry-like structure with a rough surface, you need to add an appropriate amount of F127.

[0025] Preferably, in step (1), the zinc salt is a soluble zinc salt; and the iron salt is a trivalent iron salt.

[0026] Preferably, in step (1), the stirring time is 20-40 minutes; and in step (2), the stirring time is 5-20 minutes.

[0027] Preferably, in step (3), ice-water bath ultrasound is performed at 10-20° C. for 20-40 minutes.

[0028] Preferably, in step (4), the standing time is 6-48 hours and the standing temperature is 15-30°C.

[0029] Preferably, in step (5), the heat treatment temperature is 600-1000°C, the heating rate is 1-10°C / min, and the holding time is 1-3 hours.

[0030] Preferably, in step (6), the mass ratio of the iron / cobalt / carbon composite material to sulfur powder or selenium powder is 1:2-1:5; the heat treatment temperature is 300-600°C, the heating rate is 1-10°C / min, and the insulation time is 2-5 hours.

[0031] Preferably, in step (5), the protective atmosphere for heat treatment is nitrogen or argon-hydrogen; in step (6), the protective atmosphere is nitrogen or argon-hydrogen.

[0032] In a second aspect, the present invention provides the use of the above-mentioned bayberry-shaped iron-doped cobalt-based sulfide nitrogen-doped carbon porous composite material as a negative electrode material for a sodium ion battery.

[0033] Compared with the prior art, the beneficial effects of the present invention are:

[0034] (1) The present invention prepares a FeZnCo-PBA precursor with uniform particles by a room temperature precipitation method. The preparation method is simple, the reaction conditions are simple, the morphology and size are controllable, and under the joint action of the structure directing agent PVP and the porous template F127, a stable bayberry-like Prussian blue framework structure is formed. The carbon framework obtained after heat treatment provides a continuous conductive network for cobalt disulfide (cobalt diselenide) and improves the overall structural stability of the composite material.

[0035] (2) The invention prepares a bayberry-shaped iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material or an iron-doped cobalt diselenide / nitrogen-doped carbon porous composite material as a negative electrode material for a sodium ion battery, wherein the porous carbon layer alleviates the volume expansion effect of cobalt disulfide (cobalt diselenide) during charging and discharging; and effectively increases the contact area between the active material and the electrolyte, provides abundant active sites and transmission channels, shortens the transmission path of sodium ions and enhances the connection effect. Due to the introduction of iron ions, a part of the iron ions replace the position of cobalt ions, and the electronic conductivity of cobalt disulfide (cobalt diselenide) is further improved through synergistic effects. In addition, the synergistic effect of the nitrogen-doped carbon matrix is ​​used to improve the charge transfer path and maintain the charge diffusion rate.

[0036] (3) The present invention organically combines multiple means to alleviate the volume expansion effect of cobalt-based sulfide (selenide) during the charge and discharge process and improves its conductivity, so that the composite material has a long cycle life and good electrochemical performance as a negative electrode material for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The X-ray diffraction (XRD) pattern of the bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material prepared in Example 1;

[0038] Figure 2 is a scanning electron microscope (SEM) image of the FeZnCo-PBA precursor prepared in Example 1;

[0039] Figure 3 This is a SEM image of the bayberry-shaped iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material prepared in Example 2;

[0040] Figure 4 This is a transmission electron microscope (TEM) image of the bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material prepared in Example 1;

[0041] Figure 5 This is a battery cycle performance diagram of the bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material prepared in Example 1;

[0042] Figure 6 This is a battery rate performance diagram of the bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material prepared in Example 1;

[0043] Figure 7 This is a battery cycle performance diagram of the bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material prepared in Example 2;

[0044] Figure 8 This is a battery rate performance diagram of the bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material prepared in Example 3;

[0045] Fig. 9 This is the XRD spectrum of the bayberry-like iron-doped cobalt diselenide / nitrogen-doped carbon porous composite material prepared in Example 7. DETAILED DESCRIPTION

[0046] The present invention will be further described below in conjunction with the embodiments.

[0047] Example 1

[0048] (1) 3 mmol zinc acetate, 0.6 mmol ferric chloride, 3.6 g PVP and 2 g F127 were mixed and dissolved in 100 mL deionized water, and stirred for 30 minutes to obtain a yellow transparent solution A;

[0049] (2) dissolving 2 mmol of potassium cobalt cyanide in 100 mL of deionized water by ultrasonication, stirring to obtain a transparent solution B, and dripping the solution B into the solution A prepared in step (1) under continuous stirring, stirring for another 10 minutes to form a yellow transparent solution C;

[0050] (3) subjecting the transparent solution C obtained in step (2) to ultrasonic treatment for 15 minutes in an ice-water bath to obtain a suspension C;

[0051] (4) The suspension C obtained in step (3) was allowed to stand for 24 hours, and a yellow product was obtained by centrifugation, and the product was washed three times with deionized water and anhydrous ethanol, and dried in a vacuum oven at 80° C. for 12 hours to obtain a light yellow powder α, which is a FeZnCo-PBA precursor;

[0052] (5) 0.2 g of FeZnCo-PBA was placed in a nitrogen atmosphere and heated to 800 °C for 2 h to obtain black powder β. The heating rate was 2 °C min -1 , i.e., iron / cobalt / carbon composites;

[0053] (6) Weigh 0.2 g of sulfur powder and 0.05 g of black iron / cobalt / carbon composite material, place them in the upstream and downstream of the tube furnace, and heat them in a nitrogen atmosphere at 2 °C min -1 The temperature was increased to 500°C at a heating rate and calcined for 4 hours to obtain black powder γ, that is, bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material.

[0054] Example 2

[0055] (1) 1.44 mmol zinc chloride, 0.36 mmol ferric chloride, 1.8 g PVP and 0.2 g F127 were mixed and dissolved in 50 mL deionized water, and stirred for 30 minutes to obtain a yellow transparent solution A;

[0056] (2) dissolving 1 mmol of potassium cobalt cyanide in 50 mL of deionized water by ultrasonication, stirring to obtain a transparent solution B, and dripping the solution B into the solution A prepared in step (1) under continuous stirring, stirring for another 10 minutes to form a yellow transparent solution C;

[0057] (3) subjecting the transparent solution C obtained in step (2) to ultrasonic treatment for 15 minutes in an ice-water bath to obtain a suspension C;

[0058] (4) The suspension C obtained in step (3) was allowed to stand for 24 hours, and a yellow product was obtained by centrifugation, and the product was washed three times with deionized water and anhydrous ethanol, and dried in a vacuum oven at 80° C. for 12 hours to obtain a light yellow powder α, which is a FeZnCo-PBA precursor;

[0059] (5) 0.2 g of FeZnCo-PBA was placed in a nitrogen atmosphere and heated to 800 °C for 2 h to obtain black powder β. The heating rate was 2 °C min -1 , i.e., iron / cobalt / carbon composites;

[0060] (6) Weigh 0.2 g of sulfur powder and 0.05 g of black iron / cobalt / carbon composite material, place them in the upstream and downstream of the tube furnace, and heat them in a nitrogen atmosphere at 2 °C min -1 The temperature was increased to 500°C at a heating rate and calcined for 4 hours to obtain black powder γ, that is, bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material.

[0061] Example 3

[0062] (1) 1.6 mmol zinc acetate, 0.2 mmol ferric nitrate, 1.8 g PVP and 0.6 g F127 were mixed and dissolved in 50 mL deionized water, and stirred for 30 minutes to obtain a yellow transparent solution A;

[0063] (2) dissolving 1 mmol of potassium cobalt cyanide in 50 mL of deionized water by ultrasonication, stirring to obtain a transparent solution B, and dripping the solution B into the solution A prepared in step (1) under continuous stirring, stirring for another 10 minutes to form a yellow transparent solution C;

[0064] (3) subjecting the transparent solution C obtained in step (2) to ultrasonic treatment for 17 minutes in an ice-water bath to obtain a suspension C;

[0065] (4) The suspension C obtained in step (3) was allowed to stand for 24 hours, and a yellow product was obtained by centrifugation, and the product was washed three times with deionized water and anhydrous ethanol, and dried in a vacuum oven at 80° C. for 12 hours to obtain a light yellow powder α, which is a FeZnCo-PBA precursor;

[0066] (5) 0.2 g of FeZnCo-PBA was placed in a nitrogen atmosphere and heated to 1000 °C for 1 hour to obtain black powder β. The heating rate was 5 °C min -1 , i.e., iron / cobalt / carbon composites;

[0067] (6) Weigh 0.2 g of sulfur powder and 0.05 g of black iron / cobalt / carbon composite material, place them in the upstream and downstream of the tube furnace, and heat them in a nitrogen atmosphere at 2 °C min -1 The temperature was increased to 500°C at a heating rate and calcined for 4 hours to obtain black powder γ, that is, bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material.

[0068] Example 4

[0069] (1) 1.5 mmol zinc acetate, 0.3 mmol ferric chloride, 1.8 g PVP and 1 g F127 were mixed and dissolved in 50 mL deionized water, and stirred for 30 minutes to obtain a yellow transparent solution A;

[0070] (2) dissolving 1 mmol of potassium cobalt cyanide in 50 mL of deionized water by ultrasonication, stirring to obtain a transparent solution B, and dripping the solution B into the solution A prepared in step (1) under continuous stirring, stirring for another 10 minutes to form a yellow transparent solution C;

[0071] (3) subjecting the transparent solution C obtained in step (2) to ultrasonic treatment for 18 minutes in an ice-water bath to obtain a suspension C;

[0072] (4) The suspension C obtained in step (3) was allowed to stand for 24 hours, and a yellow product was obtained by centrifugation, and the product was washed three times with deionized water and anhydrous ethanol, and dried in a vacuum oven at 80° C. for 12 hours to obtain a light yellow powder α, which is a FeZnCo-PBA precursor;

[0073] (5) 0.2 g of FeZnCo-PBA was placed in an argon-hydrogen atmosphere and heated to 800 °C for 2 h to obtain black powder β. The heating rate was 2 °C min -1 , i.e., iron / cobalt / carbon composites;

[0074] (6) Weigh 0.1 g of sulfur powder and 0.05 g of black iron / cobalt / carbon composite material, place them in the upstream and downstream of the tube furnace, and heat them in a nitrogen atmosphere at 2 °C min -1 The temperature was increased to 500°C at a heating rate and calcined for 2 hours to obtain black powder γ, that is, bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material.

[0075] Example 5

[0076] (1) 1.5 mmol zinc acetate, 0.3 mmol ferric chloride, 1.8 g PVP and 1 g F127 were mixed and dissolved in 50 mL deionized water, and stirred for 30 minutes to obtain a yellow transparent solution A;

[0077] (2) dissolving 2 mmol of potassium cobalt cyanide in 50 mL of deionized water by ultrasonication, stirring to obtain a transparent solution B, and dripping the solution B into the solution A prepared in step (1) under continuous stirring, stirring for another 15 minutes to form a yellow transparent solution C;

[0078] (3) subjecting the transparent solution C obtained in step (2) to ultrasonic treatment for 30 minutes in an ice-water bath to obtain a suspension C;

[0079] (4) The suspension C obtained in step (3) was allowed to stand for 24 hours, and a yellow product was obtained by centrifugation, and the product was washed three times with deionized water and anhydrous ethanol, and dried in a vacuum oven at 80° C. for 12 hours to obtain a light yellow powder α, which is a FeZnCo-PBA precursor;

[0080] (5) 0.2 g of FeZnCo-PBA was placed in a nitrogen atmosphere and heated to 1000 °C for 1 hour to obtain black powder β. The heating rate was 5 °C min -1 , i.e., iron / cobalt / carbon composites;

[0081] (6) Weigh 0.2 g of sulfur powder and 0.05 g of black iron / cobalt / carbon composite material, place them in the upstream and downstream of the tube furnace, and heat them in a nitrogen atmosphere at 3 °C min -1 The temperature was increased to 400°C at a heating rate and calcined for 4 hours to obtain black powder γ, that is, bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material.

[0082] Example 6

[0083] (1) 1.5 mmol zinc acetate, 0.3 mmol ferric chloride, 1.8 g PVP and 0.6 g F127 were mixed and dissolved in 50 mL deionized water, and stirred for 30 minutes to obtain a yellow transparent solution A;

[0084] (2) dissolving 2 mmol of potassium cobalt cyanide in 50 mL of deionized water by ultrasonication, stirring to obtain a transparent solution B, and dripping the solution B into the solution A prepared in step (1) under continuous stirring, stirring for another 5 minutes to form a yellow transparent solution C;

[0085] (3) subjecting the transparent solution C obtained in step (2) to ultrasonic treatment for 15 minutes in an ice-water bath to obtain a suspension C;

[0086] (4) The suspension C obtained in step (3) was allowed to stand for 24 hours, and a yellow product was obtained by centrifugation, and the product was washed three times with deionized water and anhydrous ethanol, and dried in a vacuum oven at 80° C. for 12 hours to obtain a light yellow powder α, which is a FeZnCo-PBA precursor;

[0087] (5) 0.2 g of FeZnCo-PBA was placed in a nitrogen atmosphere and heated to 800 °C for 2 h to obtain black powder β. The heating rate was 2 °C min -1 , i.e., iron / cobalt / carbon composites;

[0088] (6) Weigh 0.1 g of sulfur powder and 0.05 g of black iron / cobalt / carbon composite material, place them in the upstream and downstream of the tube furnace, and heat them in an argon-hydrogen atmosphere at 3 °C min -1 The temperature was increased to 400°C at a heating rate and calcined for 4 hours to obtain black powder γ, that is, bayberry-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material.

[0089] Example 7

[0090] (1) 1.5 mmol zinc acetate, 0.3 mmol ferric chloride, 1.8 g PVP and 0.8 g F127 were mixed and dissolved in 50 mL deionized water, and stirred for 30 minutes to obtain a yellow transparent solution A;

[0091] (2) dissolving 2 mmol of potassium cobalt cyanide in 50 mL of deionized water by ultrasonication, stirring to obtain a transparent solution B, and dripping the solution B into the solution A prepared in step (1) under continuous stirring, stirring for another 10 minutes to form a yellow transparent solution C;

[0092] (3) subjecting the transparent solution C obtained in step (2) to ultrasonic treatment for 15 minutes in an ice-water bath to obtain a suspension C;

[0093] (4) The suspension C obtained in step (3) was allowed to stand for 24 hours, and a yellow product was obtained by centrifugation, and the product was washed three times with deionized water and anhydrous ethanol, and dried in a vacuum oven at 80° C. for 12 hours to obtain a light yellow powder α, which is a FeZnCo-PBA precursor;

[0094] (5) 0.2 g of FeZnCo-PBA was placed in a nitrogen atmosphere and heated to 800 °C for 2 h to obtain black powder β. The heating rate was 2 °C min -1 , i.e., iron / cobalt / carbon composites;

[0095] (6) Weigh 0.2 g of selenium powder and 0.05 g of black iron / cobalt / carbon composite material, place them in the upstream and downstream of a tube furnace, and heat them in a nitrogen atmosphere at 2 °C min -1The temperature was increased to 400°C at a heating rate and calcined for 2 hours to obtain black powder γ, that is, bayberry-like iron-doped cobalt diselenide / nitrogen-doped carbon porous composite material.

[0096] Performance Testing

[0097] The iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material or the iron-doped cobalt diselenide / nitrogen-doped carbon porous composite material obtained in step (6) of the above embodiment is mixed evenly with the conductive agent Super P, the binder polyvinylidene fluoride (PVDF), and N-methylpyrrolidone (NMP) to obtain a slurry, which is applied on the copper current collector and dried to obtain the battery negative electrode. Glass fiber is used as the separator and 1 mol L -1 The button cell was assembled in a glove box filled with argon gas using NaPF6 as the solute and dimethyl ether as the solvent electrolyte and sodium metal as the counter electrode. The assembled sodium-ion battery was placed for 24 hours and then subjected to constant current charge and discharge test with a voltage window of 0.01 V-3V. The capacity, rate performance and charge and discharge cycle performance of the negative electrode of the sodium-ion battery were tested in an environment of 25±1℃.

[0098] The maximum discharge specific capacities of the bayberry iron-doped cobalt disulfide / nitrogen-doped carbon porous composite materials or the bayberry iron-doped cobalt diselenide / nitrogen-doped carbon porous composite materials in Examples 1-7 as sodium ion electrode materials assembled into sodium ion batteries at different current densities are shown in Table 1:

[0099] Table 1

[0100]

[0101] As can be seen from the table, changing the carbonization temperature has a certain influence on the performance of the electrode material. The reason may be that the carbonization temperature affects the degree of graphitization and thus affects the volume expansion of the carbon skeleton during the charge and discharge process. Increasing or decreasing the iron ion concentration can reduce the performance of the electrode material to a certain extent, and the performance is poor under high current. The reason may be that the optimal iron ion concentration (Zn 2+ ∶Fe 3+ =3-7:1) is more conducive to the substitution of metallic iron for metallic cobalt, which produces a synergistic effect and improves the conductivity. Therefore, increasing or decreasing the iron ion concentration will lead to poor performance of the electrode material. After the last step of sulfidation is changed to selenization, the capacity of the material is significantly reduced. This is mainly because although the sodium storage mechanism of CoSe2 and CoS2 is similar, the relative atomic mass of S is smaller than that of Se, so the theoretical sodium storage capacity of CoS2 is higher than that of CoSe2.

[0102] Figure 1 The XRD spectrum of Example 1 shows that the physical phase is cobalt disulfide with good crystallinity, and iron doping does not change the physical phase of cobalt disulfide. Figure 2This is the SEM image of the precursor of Example 1. It can be seen that the FeZnCo-PBA precursor has a bayberry-like morphology, the particles are evenly dispersed, and the average particle size is 0.5-0.9 μm; Figure 3 This is the SEM image of Example 2. It can be seen that the iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material presents a bayberry-like morphology with a rougher surface, uniformly dispersed particles, and a slightly smaller average particle size than the precursor; Figure 4 This is the TEM image of Example 1; it can be seen that the iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material shows that the cobalt disulfide particles are wrapped by the carbon layer, together forming a large carbon ball, thus showing a rough bayberry-like morphology. Figure 5 The cycle performance diagram of the sodium ion battery in Example 1 shows that the sodium ion battery has a current density of 1Ag. -1 The battery exhibited excellent electrochemical performance and maintained 600 mAh g after 300 cycles. -1 capacity. Figure 6 The rate diagram of the sodium ion battery in Example 1 is shown in FIG. -1 , 0.5Ag -1 , 1Ag -1 , 2Ag -1 , 5Ag -1 And return 0.1Ag -1 The capacity at the current density of -1 、634.5mAh g -1 、616.5mAh g -1 、585.6mAh g -1 、493.3mAhg -1 and 712.4mAh g -1 , showing excellent rate performance. Figure 7 The cycle performance diagram of the sodium ion battery in Example 2 shows that the sodium ion battery has a current density of 1Ag. -1 The electrochemical performance was good at the beginning of the cycle, with a capacity of 500 mAh g -1 After 150 cycles, the capacity began to decay to 400 mAh g -1 , stability still needs to be improved; Figure 8 The rate diagram of the sodium ion battery in Example 3; 0.2Ag -1 , 0.5Ag -1 , 1Ag -1 , 2Ag -1 , 5Ag -1 And return 0.1Ag -1 The capacity at the current density of 670.9 mAh g -1 、608.6mAh g-1 、607.7mAh g -1 、520.3mAh g -1 、400.8mAhg -1 and 665.7mAh g -1 , showing good rate performance, but the electrochemical performance of Examples 2 and 3 is lower than the best sample, indicating that the iron doping has an optimal doping ratio. Fig. 9 The XRD spectrum of Example 7 shows that the physical phase is cobalt diselenide with good crystallinity, and iron doping does not change the physical phase of cobalt diselenide.

[0103] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0104] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a bayberry-like iron-doped cobalt-based chalcogenide nitrogen-doped carbon porous composite material, characterized in that The following steps are involved: (1) Add zinc salt, iron salt, PVP and Pluronic F-127 into water and stir evenly to obtain a yellow transparent solution A; (2) dissolving potassium cobalt cyanide in water by ultrasonication to obtain a transparent solution B. Under continuous stirring, the transparent solution B is dropped into the yellow transparent solution A to form a yellow transparent solution C. (3) placing the transparent solution C obtained in step (2) in an ice water bath and sonicating to obtain a suspension C; (4) The suspension C obtained in step (3) is allowed to stand, and then washed and dried to obtain a light yellow powder α, which is a bayberry-like FeZnCo-PBA precursor; (5) heat treating the light yellow powder α obtained in step (4) under a protective atmosphere to obtain a black powder β, i.e., an iron / cobalt / carbon composite material; (6) The black powder β obtained in step (5) is heat-treated with sulfur powder or selenium powder under inert gas protection to obtain black powder γ, i.e., a myrica-like iron-doped cobalt disulfide / nitrogen-doped carbon porous composite material or a myrica-like iron-doped cobalt diselenide / nitrogen-doped carbon porous composite material.

2. The preparation method according to claim 1, characterized in that: In steps (1) and (2), Fe 3+ and Zn 2+ The molar ratio is 1:15-1:3; The mass ratio of PVP to Pluronic F-127 is 1.8:1-3.6:1; The total molar ratio of potassium cobalt cyanide to metal ions is 4:5-2:3; The mass ratio of potassium cobalt cyanide to PVP is 1:4-1:

10.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the zinc salt is a soluble zinc salt; and the iron salt is a trivalent iron salt.

4. The preparation method according to claim 1, characterized in that: In step (1), the stirring time is 20-40 minutes; In step (2), the stirring time is 5-20 minutes.

5. The preparation method according to claim 1 or 2, characterized in that: In step (3), ice water bath sonication is performed at 10-20°C for 20-40 minutes.

6. The preparation method according to claim 1 or 2, characterized in that: In step (4), the standing time is 6-48 hours, and the standing temperature is 15-30°C.

7. The preparation method according to claim 1 or 2, characterized in that: In step (5), The heat treatment temperature is 600-1000 ℃, the heating rate is 1-10 ℃ / min, and the holding time is 1-3 hours.

8. The preparation method according to claim 7, characterized in that: In step (6), The mass ratio of the iron / cobalt / carbon composite material to the sulfur powder or selenium powder is 1:2-1:5; The heat treatment temperature is 300-600 ℃, the heating rate is 1-10 ℃ / min, and the holding time is 2-5 hours.

9. The preparation method according to claim 1 or 2, characterized in that: In step (5), the protective atmosphere for heat treatment is nitrogen or argon hydrogen; In step (6), the protective atmosphere is nitrogen or argon hydrogen.

10. Use of the bayberry-shaped iron-doped cobalt-based chalcogenide nitrogen-doped carbon porous composite material obtained by the preparation method according to claim 1 or 2 as a negative electrode material for sodium ion batteries.